2015
DOI: 10.1155/2015/262654
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid Tumor of the Popliteal Fossa during Pregnancy

Abstract: Desmoid tumors are fibroblastic neoplasms that have an intermediate behavior with a highly aggressive infiltrative growth arising from deep muscle or aponeurosis. We present the case of a 34-year-old woman that developed a painless mass in the right popliteal fossa during pregnancy after intracytoplasmic sperm injection and hormonal therapy. The MRI scan showed a hyperintense mass of 6,7 cm × 4,7 cm × 3,8 cm surrounding the lateral head of the gastrocnemius muscle. The open biopsy was done one week after deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Although lacking metastatic potential, it typically widely infiltrates into soft tissues, frequently encompassing neurovascular structures. [3][4][5]12,[23][24][25]27,[29][30][31][32] It can compress, encompass, or invade nerves or track along them, making it difficult to achieve complete excision without compromising nerve function. Recurrence typically happens locally but can occur at distant sites as well, either synchronously or metachronously.…”
mentioning
confidence: 99%
“…Although lacking metastatic potential, it typically widely infiltrates into soft tissues, frequently encompassing neurovascular structures. [3][4][5]12,[23][24][25]27,[29][30][31][32] It can compress, encompass, or invade nerves or track along them, making it difficult to achieve complete excision without compromising nerve function. Recurrence typically happens locally but can occur at distant sites as well, either synchronously or metachronously.…”
mentioning
confidence: 99%
“…Out of the 50 cases in the study, the most common site was the abdominal muscles, particularly the right rectus muscle [ 12 ]. There are rare cases reported of desmoid tumors in extra-abdominal sites such as the vulva, larynx, neck, and popliteal fossa [ 13 , 14 ]. Furthermore, a recent study involving 382 patients with desmoid-type fibromatosis found that the prevalence of pain was only 36%, thereby highlighting the relatively uncommon nature of this symptom in the condition [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…With an incidence rate of approximately five per million people annually, it is uncommon, representing approximately 0.3 per cent of all soft tissue neoplasms (18,19). While the exact causes remain elusive, desmoid-type fibromatosis is currently considered to be associated with surgical history, traumatic injury, familial adenomatous polyposis and Gardner's syndrome (10). Women were more likely to develop the disease compared with men (20), and therefore, estrogen is an influencing factor.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complaints of patients are painless progressive growth of the mass, neurological dysfunction, joint stiffness and abdominal discomfort due to the tumor growth (9). The imaging findings of desmoid-type fibromatosis depend on the number of fibroblasts proliferating in the tumor, as well as the fiber composition, collagen content and tumor supply (10). Areas of dense fibrous tissue and scar-like collagen fiber deposition usually show low signal for T1WI and T2WI, and no enhancement after injection of contrast agent (11).…”
Section: Introductionmentioning
confidence: 99%